2020
DOI: 10.1111/ced.14360
|View full text |Cite
|
Sign up to set email alerts
|

‘Cell‐phone acne’ epidemic during the COVID‐19 pandemic

Abstract: As the world plunges into the longest and the biggest lockdown in world’s history, most of us are turning towards an increased use of mobile phones as the most convenient way to stay connected. However, this convenience is also taking a toll on the overall skin health, particularly in the patients of acne.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…Acne generally experienced by adolescents and young adults (12-25 years old) [10]. The ratio of the incidence of cell phone acne between women and men in this study is 8:5 [4].…”
Section: Epidemiologymentioning
confidence: 54%
See 4 more Smart Citations
“…Acne generally experienced by adolescents and young adults (12-25 years old) [10]. The ratio of the incidence of cell phone acne between women and men in this study is 8:5 [4].…”
Section: Epidemiologymentioning
confidence: 54%
“…Singh et al recently in 2020 reported an acne epidemic with unilateral predominance due to cell phone use during the COVID-19 pandemic. In this study, acne lesions were in the form of new acne eruptions or acne flares with a more severe degree of severity on the side of the face that was more frequently in contact with cell phone [4].…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations